Effectiveness of Digital Health Interventions in Managing Glycated Haemoglobin: A Randomized Controlled Trial - Qasim Abbas Khyoosh Al-Eqabi; Shatha Mahmood Niazy; Mohammed Malih Radhi (Medsci Publications, 2024)
Background: Digital health interventions, such as mobile apps and wearable devices, have emerged as potential tools to help individuals manage glycemic control. By comparing the outcomes of participants using digital health tools with those following traditional methods of diabetes management. The study aimed to evaluate the impact of digital interventions on Managing Glycated Haemoglobin control. Methodology: A randomized, controlled trial was conducted at the Babylon Diabetes and Endocrinology Center/ Iraq. Participants were selected based on established inclusion and exclusion criteria and were assigned to either the intervention or control groups through randomization. The intervention group received a medication management app specifically designed for smartphones. Data were collected over six months through three tests and analyzed using SPSS-20. Results: The study found no significant difference in HbA1c levels between the intervention and control groups during the pre-test period. However, significant differences emerged at both post-test I (after 3 months) and post-test II (after 6 months), with the intervention group showing a significant decrease in HbA1c levels from pre-test to both post-test I and post-test II. Conclusions: The study underscores the need to use digital health interventions in diabetes management to improve the quality of patient care. Decision-makers can improve the quality of blood sugar control and overall health by keeping up with such smart applications.